Integrating Passive Biomonitoring and Active Monitoring: Spider Web Silk and Portable Instruments for Air Quality in Urban Areas - Amina Muzamil; Khawar Sultan; Abeer Hashem; Graciela Dolores Avila-Quezada; Elsayed Fathi Abd-Allah; Qamar uz Zaman (Water, Air, & Soil Pollution, 2024)
Urban areas worldwide face significant challenges from increasing air pollution, posing health risks and environmental concerns. Lahore, a major city in Pakistan, is particularly affected by severe air pollution due to rapid industrial growth, high vehicle emissions, and various human activities. Traditional air quality monitoring methods, while effective, are often costly and complex, limiting their widespread use. This study investigates a dual monitoring system combining passive biomonitoring with spider web silk and active measurements using portable instruments to assess airborne pollutants in urban environments. Spider webs, collected from various sites in Lahore, were analyzed for heavy metals, while portable instruments simultaneously measured PM 2.5 , PM 10 , total volatile organic contents, formaldehyde, and carbon monoxide at the same locations. A spatial distribution analysis using GIS and statistical analysis revealed a pattern with significant changes as per land use in the urban environment related to anthropogenic activities. The Principal Component Analysis revealed three distinct clusters of pollutants origins consisting of: I) effluent drains and landfills, II) construction sites, and III) residential areas. The concentrations of Hg in spider silk (average ~ 2.66 mg/kg) were found to be significantly higher in the northeastern part of Lahore, with a similar trend observed in Cd, Cu, Ni, and As levels (average ~ 15.45, 102.87, 31.72, and 6.64, respectively). Several-fold changes in levels and spatial distribution of Pb (15.12 to 356.41 mg/kg) showed a higher concentration in the northern and northeastern parts of Lahore. The spatial variation pattern of Cr (average~ 57.04 mg/kg) registered a higher concentration in southwestern Lahore. Ambient air levels of measured pollutants followed almost similar patterns in spatial distribution. PM 2.5 and PM 10 measured higher levels (195 and 226 μg/m 3 , respectively) in the southwestern and northwestern areas, with a similar pattern of variation observed in TVOC (average ~ 0.14 μg/m 3 ). The concentration of HCHO (average ~ 0.003 μg/m 3 ) was higher in the southwest of Lahore. All measured pollutants registered higher values than air quality standards. Particulate matter is the most dominant pollutant contributing to air pollution (up to 20x higher than WHO guidelines). The findings support the use of a dual monitoring system, integrating passive spider web silk biomonitoring and active portable instruments, as a scalable and sustainable solution for air quality management. This approach holds potential for global application in diverse urban environments, with future research focusing on further validation and integration with advanced remote sensing technologies to enhance air quality monitoring and contribute to improved public health and environmental management worldwide. Hence, this research work points to the potential use of spider silk as a biomonitoring tool in combination with instrumental measurement of ambient air pollutants.